Nomenclature for renal replacement therapy and blood purification techniques in critically ill patients: practical applications. Issue 1 (December 2016) - Villa, Gianluca; Neri, Mauro; Bellomo, Rinaldo; Cerda, Jorge; De Gaudio, A.; De Rosa, Silvia; Garzotto, Francesco; Honore, Patrick; Kellum, John; Lorenzin, Anna; Payen, Didier; Ricci, Zaccaria; et al.
Abstract This article reports the conclusions of the second part of a consensus expert conference on the nomenclature of renal replacement therapy (RRT) techniques currently utilized to manage acute kidney injury and other organ dysfunction syndromes in critically ill patients. A multidisciplinary approach was taken to achieve harmonization of definitions, components, techniques, and operations of the extracorporeal therapies. The article describes the RRT techniques in detail with the relevant technology, procedures, and phases of treatment and key aspects of volume management/fluid balance in critically ill patients. In addition, the article describes recent developments in other extracorporeal therapies, including therapeutic plasma exchange, multiple organ support therapy, liver support, lung support, and blood purification in sepsis. This is a consensus report on nomenclature harmonization in extracorporeal blood purification therapies, such as hemofiltration, plasma exchange, multiple organ support therapies, and blood purification in sepsis.